If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + 3) + -4(2 + -3x) = 6 + x Reorder the terms: 2(3 + 2x) + -4(2 + -3x) = 6 + x (3 * 2 + 2x * 2) + -4(2 + -3x) = 6 + x (6 + 4x) + -4(2 + -3x) = 6 + x 6 + 4x + (2 * -4 + -3x * -4) = 6 + x 6 + 4x + (-8 + 12x) = 6 + x Reorder the terms: 6 + -8 + 4x + 12x = 6 + x Combine like terms: 6 + -8 = -2 -2 + 4x + 12x = 6 + x Combine like terms: 4x + 12x = 16x -2 + 16x = 6 + x Solving -2 + 16x = 6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -2 + 16x + -1x = 6 + x + -1x Combine like terms: 16x + -1x = 15x -2 + 15x = 6 + x + -1x Combine like terms: x + -1x = 0 -2 + 15x = 6 + 0 -2 + 15x = 6 Add '2' to each side of the equation. -2 + 2 + 15x = 6 + 2 Combine like terms: -2 + 2 = 0 0 + 15x = 6 + 2 15x = 6 + 2 Combine like terms: 6 + 2 = 8 15x = 8 Divide each side by '15'. x = 0.5333333333 Simplifying x = 0.5333333333
| 14-2(3p+p)=6(4+p) | | 5(2x+8)=7x+20 | | 0.05x+0.04y=420 | | -7-2x=-19 | | -1(3z+4)=6z+-3(3z+2) | | 3(2x+4)-x=11 | | f(x)=3x^2+6x-7 | | 5c-4(9-c)= | | 5c+4c= | | 3(2x+5)-x=11 | | 5c+4n= | | [x-3]=12 | | z+30=16 | | 14+3n=8n-3(1n-4) | | 17=2x+3 | | 4(2x+1)=x+4 | | 18-10(x-1)=4x | | 2-4/2 | | 1/3(5y-1) | | 8+f(4/5)=0 | | -8x-(3x+6)=4-1x | | 5x-4=1-x | | (y^2-4y+3)/(5y^2-40y+35) | | 4y-3(2y-7)=5y+12 | | v^2-v=30 | | x-5+3x/4=-5+7x/4 | | x+2-8=14 | | 28+a+(-48.08)*(1.414213562)=0 | | 2t+3=-12 | | 34+a+(-48.08)*(1.414213562)=0 | | 5(-3b+2)=40 | | 34+a+(-48.08)*1.414213562=0 |